Current Understanding of BEOL TDDB Lifetime Models. (1st January 2015) - Croes, K.; Wu, C.; Kocaay, D.; Li, Y.; Roussel, Ph.; Bömmels, J.; Tőkei, Zs.
Abstract : We summarize the current understanding of BEOL TDDB lifetimes models. We first review long-term TDDB data studying the intrinsic reliability behavior of low-k materials, where imec's so-called p-cap test vehicle was employed. Then, damascene data, where copper lines are integrated in the low-k materials, are discussed. When simply assuming that the electric field scales inversely proportional with spacing, not taking into account the impact of process variability like line-edge-roughness, line-to-line overlay errors and via-to-line misalignment, the impact damage model and the power law fit the available data in the best way over the wide range of applied fields. Finally, we discuss the eventual impact of this process variability on the assessment of life-time models and make recommendations for future work.